EVALUATION OF ANTAGONISTIC POTENTIALITY OF SOME NATURAL PLANT EXTRACTS AGAINST FUSARIUM OXYSPORUM F. SP. LINI - S.K. DWIVEDI; SANGEETA (International Journal of Pharma and Bio Sciences, 2014)
The effectiveness of aqueous extract of seven locally available medicinal plants i.e. Trachyspermum ammi (seeds), Zingiber officinale (rhizome), Tinospora cordifolia (leaves), Cymbopogon citratus (leaves), Moringa oleifera (bark) were evaluated against the plant pathogenic fungus i.e. Fusarium oxysporum f. sp. lini (causing wilt in linseed). The plant extracts were screened for their antagonistic property against the mycelial growth of the Fusarium oxysporum f. sp. lini at four different concentrations i.e. 10, 25, 50 and 75 percent by using poisoned food technique. The results of this study have shown that all the five plant extracts significantly (p ≤ 0.01) inhibited the growth of the test pathogen. It was observed that Tinospora cordifolia (leaves), Cymbopogon citratus (leaves) and Moringa oleifera (bark) completely inhibited the growth of pathogen at 75% concentration whereas Zingiber officinale (rhizome) caused 89.65% inhibition followed by Trachyspermum ammi (seeds) (82.50%) on the eighth day of inoculation.